Production and characterization of aluminum powder derived from mechanical saw chips and its processing through powder metallurgy (2020)
Sawing is the most common technique used to break down metals before manufacturing processes, and it produces a considerable amount of wasted aluminum in the form of chips. These chips are small and semi continuous, so they are not suitable for recycling by melting. Therefore, the aim of this paper is to study the recyclability through powder metallurgy techniques of aluminum chips left over from sawing processes, studying the influence of grinding time on the properties of both the aluminum powder and the sintered materials. Grinding was performed in ball mill using a rotational speed of 55 rpm at different grinding times. The cold compaction process was performed applying 800 MPa of pressure. The cylindrical samples were sintered using argon as the inert gas at a temperature of 620 °C for 1 h. We conclude that aluminum chips from the sawing process are suitable for recycling through powder metallurgy techniques.